Dementia among migrants and ethnic minorities in Italy: rationale and study protocol of the ImmiDem project. Issue 1 (7th January 2020) - Canevelli, Marco; Lacorte, Eleonora; Cova, Ilaria; Cascini, Silvia; Bargagli, Anna Maria; Angelici, Laura; Giusti, Angela; Pomati, Simone; Pantoni, Leonardo; Vanacore, Nicola
Abstract : Introduction: Due to the ongoing demographic and epidemiological transitions, estimating the phenomenon of dementia in migrants and minority groups, exploring its characteristics and challenges and implementing dedicated healthcare policies, constitute emerging and urgent matters for Western countries. In the present paper we describe the rationale and design of the 'Dementia in immigrants and ethnic minorities living in Italy: clinical-epidemiological aspects and public health perspectives" (ImmiDem) project. Methods and analysis: Three main aims will be pursued by the ImmiDem project. First, a survey of all Italian dementia services will be conducted with dedicated questionnaires in order to estimate and describe the proportion and characteristics of migrants seeking help for cognitive disturbances. The different clinical approaches for diagnosing dementia and the challenges encountered in the assessment of cognitive functioning and in the provision of care in these groups of individuals will also be investigated. Second, record linkage procedures of data routinely collected in regional Health Information Systems will be conducted in order to identify and monitor migrant individuals with dementia living in the Lazio region. Third, tailored national and local care-coordination pathways and/or good practices dedicated to migrants affected by dementia and cognitive disorders will be identified and promoted. Ethics and dissemination: The study protocol was approved by the Ethics Committee of the Italian National Institute of Health (protocol 10749; 5 April 2018). The project was launched in November 2018 and will end in November 2021. The findings of the project will be disseminated through scientific peer-reviewed journals as well as to the public via the Dementia Observatory website (https://demenze.iss.it ).